2012
DOI: 10.1177/0194599812443353
|View full text |Cite
|
Sign up to set email alerts
|

Early Adoption of Transoral Robotic Surgical Program

Abstract: The initiation of a TORS program in the post-FDA setting can be achieved in a safe and efficient manner. Early results of pioneering TORS centers are reproducible. Continued investigation of TORS as a treatment option for oropharyngeal carcinoma is warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
16
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 32 publications
4
16
0
Order By: Relevance
“…7, 8). Use of this technique provided for a rate of exposure adequacy, exposure time, operative time, completeness of resection, and functional outcomes that fall well within the range of those published by experienced centers using a variety of different mouth gags [2][3][4][5][6][7][8]. Indeed, the exposure time is actually somewhat lower than those previously reported.…”
Section: Discussionsupporting
confidence: 56%
“…7, 8). Use of this technique provided for a rate of exposure adequacy, exposure time, operative time, completeness of resection, and functional outcomes that fall well within the range of those published by experienced centers using a variety of different mouth gags [2][3][4][5][6][7][8]. Indeed, the exposure time is actually somewhat lower than those previously reported.…”
Section: Discussionsupporting
confidence: 56%
“…27,30,42,61,62,7274 Swallowing-related QOL is reported to decrease immediately following TORS, but has been demonstrated to improve by 1 year post treatment, with possible further improvement thereafter 79. In the study of Cognetti et al,58 most patients resumed oral intake by postoperative day 1, with 91% of patients tolerating oral intake at the first postoperative visit. In the 12 patients who were taking an oral diet with tube feed supplementation, the PEG tube had been placed for anticipated adjuvant therapy with chemoradiation based on clinical staging.…”
Section: Functional Outcomes (Table 4)mentioning
confidence: 99%
“…Later, O’Malley and colleagues 14 reported the technical feasibility of robot-assisted surgery for base of tongue (BOT) neoplasm resection; Weinstein and colleagues 15 successfully performed a robot-assisted radical tonsillectomy in 2007 after cadaveric robotic surgery. With this much groundwork completed, several studies subsequently focused on the application of TORS in various types of neoplasms, including squamous cell carcinoma, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 45, 46, 47, 48, 49, 50, 51, 52, 53, 54, 55, 56, 57, 58, 59 mucoepidermoid carcinoma, 16, 35, 43, 50, 60, 61 malignant melanoma, 62 synoviosarcoma, 33, 63 adenoid cystic carcinoma, 33, 35, 43, 50, 60, 64 pleomorphic adenoma, 32, 35, 47, 65 lipoma 33 and neurilemmoma. 64 …”
Section: Clinical Applications Of Robotic Surgery In the Head And Neckmentioning
confidence: 99%
“…Several subsequent reports showed favorable results, such as short hospital stays, quick functional recovery and a lack of significant complications, when parapharyngeal neoplasms (squamous cell carcinoma, lipoma, pleomorphic adenoma, adenoid cystic carcinoma, cartilaginous tumor and neurilemmoma) were removed using the robot. 36, 61, 73, 74, 75 Chan et al 76 reported that 24% of patients with pleomorphic adenoma experienced unexpected capsule breakage or neoplasm fracture during surgery, potentially resulting from an inability to safely grasp the tumor, sharp instruments and a lack of tactile and haptic feedback.…”
Section: Clinical Applications Of Robotic Surgery In the Head And Neckmentioning
confidence: 99%